ESPOROTRICOSE FELINA NO ESTADO DO ESPÍRITO SANTO - BRASIL: CARACTERÍSTICAS CLÍNICO-EPIDEMIOLÓGICAS, MICROBIOLÓGICAS E AVALIAÇÃO DA ACURÁCIA DO EXAME CITOPATOLÓGICO COMO FERRAMENTA DIAGNÓSTICA - Rediguieri, Bruno Carneiro (2021)
Sporotrichosis is an implantation mycosis caused by species of the Sporothrix schenckii complex, which mainly affects the skin and subcutaneous tissue of humans and homeothermic animals. Classically, the disease is acquired by inoculation of the microorganism in the subcutaneous tissue, in traumatic contact with contaminated soil, vegetation, and decomposing material. The alternative route of transmission (zoonotic) occurs frequently by scratching or biting of cats infected with Sporothrix brasiliensis, a more virulent species. Feline sporotrichosis is an endemic disease in Brazil, including the state of Espírito Santo, with an alarming increase in cases. The objective of this study was to verify the clinical-epidemiological and microbiological aspects of feline sporotrichosis in ES, as well as to demonstrate the degree of reliability of the cytopathological examination in the diagnosis of the disease. From March 2019 to April 2020, 154 suspicious cases from several municipalities in ES were evaluated. The animals were examined and, after collecting clinical-epidemiological data, subject to the collection of biological samples and making slides by imprint, to perform the cytopathological examination associated with the quick panoptic technique. The slides were blindly assessed by two researchers. Part of the sample was sown on Sabouraud agar (ASD) and the recovered Sporothrix isolates were morphological and molecularly characterized. The isolates were identified by species-specific PCR targeting a fragment of the calmodulin gene (CAL). A digital public image bank was created using the online tool Padlet, to document different types of animal injuries and positive slide profiles. The degree of reliability of the cytopathological examination concerning the culture was assessed using the degree of agreement between observers. The degree of agreement was defined by the Kappa agreement coefficient. Accuracy parameters of the method were determined using the Chi-square independence test. Of the 154 cats, the majority were male (n = 109; 70.8%), non-neutered (n = 132; 85.7%), of semihousehold habit (n = 116; 75.3%), of urban area (n = 150; 97.4%) and with responsible guardian (n = 137; 89.0%). The average age of the animals was 25.3 months. One hundred and sixteen (75.3%) samples were positive in cytopathology for sporotrichosis, while 121 (78.6%) were confirmed in the culture. The interobserver agreement was high (Kappa coefficient = 0.96). Sensitivity, specificity, predictive (positive and negative) and accuracy values were 95.0%, 97.0%, 99.1%, 84.2% and 95.5%, respectively. All Sporothrix isolates evaluated by molecular assay were identified as S. brasiliensis. We concluded that the cytopathological examination by imprint, associated with the quick panoptic technique, demonstrated a high degree of reliability, regardless of the severity of the clinical condition. Furthermore, the speciesspecific PCR technique used was able to identify S. brasiliensis quickly and at a low cost. Finally, this species seems to be the unique agent of feline sporotrichosis in the State of ES.